Pengaruh Intensitas Mengakses Media Sosial Youtube dan Komunikasi Peer Group Terhadap Prestasi Belajar Siswa - Anggita Primartiwi; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Social media or the so-called social networking sites (SNS) is one of the media which is experiencing the fastest rise. One of them is the Youtube social media which has increased the number of its users each year. The ease of access to the Internet, especially social media is not always a positive effect since nearly 80% of teenagers aged 10-19 in 11 provinces of Indonesia are addicted to social media and the majority of these teenagers use social media for inappropriate things. The high use of social media among teenagers become a thing to be considered since a large amount of time spent by teenagers to use social media can have an impact on their daily activities like their study time as a student. The lack of learning time for the student may have an impact on student achievement becoming not optimal. In addition to the tools and technologies of social media, the school environmental factors, especially peers become one of the factors that affect student achievement. Peer influence can determine how a student takes an attitude or behavior. Communication with peers can provide positive and negative impacts. This study aims to determine whether there is an effect of the intensity of accessing Youtube social media and Peer Group Communication on student achievement. The theory used in this study is Social Media Framework Theory to assess the effect of the intensity of accessing Youtube social media on student achievement and the Theory of Reference Group to assess the intensity of communication peer group on student achievement. The sampling technique used nonprobability sampling conducted by accidental sampling with a sample size of 100 people with the criteria of high school students aged 15-19 years in Yogyakarta and social media users of Youtube. The test is carried out using the Simple Linear Regression Test. The results showed that there was a negative effect of the intensity of accessing Youtube social media on student achievement with a significance value of 0.104. The intensity variable of accessing Youtube social media on student achievement contributed 4,9%. The remaining 94% contribution is influenced by other variables not examined in this study. The biggest contributory factor of the intensity variables of accessing Youtube social media on student achievement is the duration and frequency of access to social media. This is because students are allowed to bring gadgets to school. The research results of the intensity of peer group communication showed insignificant results. That is the intensity of peer group communication did not effect on student achievement with a significance value of 0.107 which exceeded the 0.05 standard of significance. For further research, it is expected to examine more of the other factors beyond these studied factors that can affect student achievement.